Analysis of New Student Admission Service Management Using The ITIL Version 3 Framework in The Service Design Domain at Senior High School of 22 Palembang - Akbar, Marutha Berlianti; Sutabri, Tata (Media Jurnal Informatika, 2023)
This study aims to analyze and evaluate the management of new student admission services at SMA Negeri 22 Palembang using the ITIL Version 3 Framework in the Service Design domain. The problem of this research is that there is no connection between the school website and the PPDB Online application owned by the government, and there is a decrease in bandwidth when using the application together when registration is carried out for new students. This research uses a qualitative approach by collecting data through interviews, observation, and analysis. The results showed that the application of ITIL in the management of new student admission services can improve the efficiency and quality of services ensuring the fulfillment of the needs of prospective students and parents, as well as strengthening the relationship between schools and communities around Talang Kelapa, Palembang. The conclusion of this research is that the use of ITIL in the management of new student admission services at SMA Negeri 22 Palembang can provide benefits for SMA Negeri 22 Palembang to improve services for new student admissions, and to have a positive impact on the community's view of SMA Negeri 22 Palembang.